Muhadharah Sebagai Upaya Pengembangan Public Speaking Pada Santri di Pondok Pesantren Yanbuul Ulum, Siak, Riau - Yosepin, Pipin; Husna, Lutfia (Journal of Communication Studies, 2023)
In developing themselves, students are required to have the ability to speak in public. Self-confidence is important for a student to have in order to be able to improve communication techniques as a form of cadre training for preaching training. This article describes efforts to develop public speaking among students in muhadharah activities at the Yanbuul Ulum Islamic Boarding School, Siak Riau. The purpose of this writing is to find out the extent to which muhaharah activities for students have an impact when speaking in public. The method used in this research is descriptive qualitative. Data collection techniques are carried out by observation, interviews and documentation. Interviews were conducted with 7 informants consisting of the Islamic boarding school principal, supervisor and 5 santri. The results of the research show that 1) Routine muhadharah activities for students are able to change the mentality of students who previously lacked self-confidence to become more confident. 2) Students are able to overcome obstacles in public speaking and can speak fluently in public. 3) In giving speeches, students can be creative in choosing materials and methods of preaching each week according to the events required. Muhadharah activities at the Yanbuul Ulum Islamic boarding school, Siak Riau are very effective in training students' public speaking. Students are more confident when giving speeches and are creative in choosing preaching methods according to the needs of the event. Students are expected to be able to develop themselves into professional da'wah agents.